Bilateral Bell's Palsy A Case Report - Babiker Ali, Ali (Gezira Journal of Health Sciences, 2021)
We report a case of 12 years Sudanese boy who presented with acute onset of bilateral isolated facial palsy. He had all his vaccines including polimyelitis vaccine. His past history is of no significance, his systemic examination was normal. He responded to a short course of prednisolone. In three months time he showed complete recovery with no residual effects.